الثقافة التنظيمية وعلاقتها بالفعالية التنظيمية دراسة ميدانية لدى عمال مديرية نقل وتوزيع الكهرباء والغاز لولاية معسكر - يمينة ., حطاب (Université de M'sila, 2019)
ملخص: هدفت هذه الدراسة إلى التعرف على العلاقة بين الثقافة التنظيمية بأبعادها (النظام الرمزي، القيّم المهنية ومعايير التصرف، المعتقدات الأولية) بمتغير الفعالية التنظيمية وبعديها (بعد اقتصادي، بعد سلوكي) لدى عينة تكونت من 96 عمال مديرية نقل وتوزيع الكهرباء والغاز من مختلف المستويات الإدارية باستخدام المنهج الوصفي، وقد تم الاعتماد في بناء أداتي البحث (الاستبيان) على دراسة كل من hofsted1990 في الثقافة التنظيمية و Steers (1977) فيما يخص الفعالية التنظيمية. توصلت النتائج إلى وجود علاقة إرتباطية بين الثقافة التنظيمية والفاعلية التنظيمية وهذا من خلال استعمال معامل الارتباط بيرسون Abstract :This study aimed to identify the relationship between the organizational culture in its dimensions (symbolic system, professional values and standards of conduct, initial beliefs) with the variable regulatory effectiveness and its dimension (after economic, after behaviour) in a sample of 96 workers of the Directorate of Electricity and Gas Transmission and Distribution of Various Management levels using the descriptive approach, the construction of the two research instruments (questionnaire) has been based on the study of both hofsted1990 in organizational culture and Steers (1977) for organizational effectiveness. The results found a correlation between organizational culture and organizational effectiveness through the use of pearson correlation coefficientJEL Classification.
Keywords: الكلمات المفتاحية : الثقافة التنظيمية، الفعالية التنظيمية، النظام الرمزي، القيّم المهنية ومعايير التصرف، المعتقدات القاعدية، بعد اقتصادي، بعد سلوكي.